Analysis Of Science Process Skills In Hands On Activity In Application Of The Pode Model In Elementary School - Fiky Herdianto; Hartono Hartono; Ali Sunarso (Eduvest - Journal of Universal Studies, 2021)
The low learning outcomes of science in grade IV elementary school. The learning process still uses conventional methods which can cause students to be less directly involved in direct practical activities and active discussion during learning. It is necessary to apply the Hands On Activity approach in the application of the PODE model to improve students' science process skills. The purpose of this study was to analyze the science process skills in Hands On Activity in the application of the PODE learning model in elementary schools. This type of research is a Quasi Experimental Design in the form of Nonequivalent Control Group Design. The sample in this study amounted to 60 fourth grade students. Data collection techniques using observation sheets, indicators of science process skills consist of observing, classifying, experimenting, communicating and concluding. Data analysis used simple and multiple linear regression test. The results showed that the science process skills of the experimental class applying Hands on Activity and the PODE model were 76.4% and 61.2%, while the PODE model control class had an effect of 50.7%. The results of multiple linear tests obtained results of 76.5%, the results of Sig. Simultaneous effect test is 0.000 < 0.05 and Fcount 43.897 > Ftable 3.33, and it can be concluded that there is an effect of Hands on Activity (X1) and PODE model (X2) simultaneously on science process skills.